2019
DOI: 10.1016/j.jpowsour.2019.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Operando flow regime diagnosis using acoustic emission in a polymer electrolyte membrane water electrolyser

Abstract: Polymer electrolyte membrane water electrolysers (PEMWE) are a key technology for producing clean ('green') hydrogen for decarbonisation of the transport sector and grid stabilization utilising increasing levels of renewable energy. Understanding the complex interplay of factors that affect device operation is key to improving the technology and advanced diagnostic techniques have a major role to play. In this work, acoustic emission analysis is used as a non-destructive, operando diagnostic tool to provide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…To do this, the land locations are focused on as the open flow channels are dominated by relatively unstable twophase flow with time-varying bubble dynamics, which precludes accurate analysis of the effective water thickness in the LGDL. Indeed, flow dynamics within channels have been extensively studied using optical cells [34,[40][41][42], but it is the particular ability of neutron imaging to examine water under lands and within porous structures that is exploited here [17,19].…”
Section: Neutron Imaging and Image Analysismentioning
confidence: 99%
“…To do this, the land locations are focused on as the open flow channels are dominated by relatively unstable twophase flow with time-varying bubble dynamics, which precludes accurate analysis of the effective water thickness in the LGDL. Indeed, flow dynamics within channels have been extensively studied using optical cells [34,[40][41][42], but it is the particular ability of neutron imaging to examine water under lands and within porous structures that is exploited here [17,19].…”
Section: Neutron Imaging and Image Analysismentioning
confidence: 99%
“…In previous work, the authors demonstrated the ability of AE to detect changes in the number and size of bubbles passing through the flow channel of a PEMWE. This enabled the prediction of the change from bubbly to slug flow and showed that AE is a valuable operando tool for PEMWE diagnosis (Maier et al, 2019). Here, we demonstrate that AE signal changes dramatically when, rather than normal two-phase flow, stagnant bubbles are located within the vicinity of AE sensor.…”
Section: Introductionmentioning
confidence: 58%
“…This significant decrease of acoustic hits highlights a dramatic change of two-phase flow within the flow channels. The relationship between the number of acoustic hits and the number of bubbles passing through the flow channels has been established in previous work (Maier et al, 2019), which found that the number of acoustic hits scales directly with the number of bubbles passing through the flow channels. Hence, a drop in the number of acoustic hits indicates a decrease in the number of bubbles generated and passing through the flow channels, which is likely due to the blocking of the flow FIGURE 2 | Typical structure of an acoustic hit as voltage profile as a function of time.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Polymer electrolyte membrane water electrolysers (PEMWEs) are considered a highly promising technology for 'green' energy generation from renewable but intermittent energy sources such as solar and wind. PEMWEs possess several key advantages over conventional alkaline electrolysers, including high operational current density, high conversion efficiency, high purity of produced gases, rapid response, compact structure and high reliability [1][2][3][4][5][6][7]. Moreover, PEMWEs are robust and amenable to coupling with PEM fuel cells to create highly efficient regenerative energy storage systems.…”
Section: Introductionmentioning
confidence: 99%